2021
DOI: 10.1111/ijcp.14354
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the evidence‐based practices attitude scale‐15 in Turkish family medicine residents

Abstract: Aims: Aim of this study is to translate and apply a cross-cultural adaptation of the Evidence-Based Practice Attitude Scale (EBPAS) in Turkish and investigate its validity and reliability. Methods:The original EBPAS-15 (a questionnaire assessing health professionals' attitudes to implementation of evidence-based practice) was translated into Turkish.To assess its validity and reliability, 151 family medicine residents answered the EBPAS-15 by web-based survey. In addition, relationships of family medicine resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To test internal consistency of the items, most studies calculated and reported a Cronbach’s alpha ( n = 67), and two studies calculated and reported a person separation index. The quality of internal consistency calculations was rated as “very good” in 64 studies [ 36 39 , 41 45 , 47 – 63 , 66 , 67 , 69 , 71 81 , 83 , 84 , 86 , 88 92 , 94 , 95 , 97 , 99 102 , 104 106 , 108 , 110 ] and as “inadequate” in five studies [ 46 , 60 , 98 , 109 , 111 ]. Inadequate ratings were given when a Cronbach’s alpha was not reported for each unidimensional subscale in a multidimensional instrument [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…To test internal consistency of the items, most studies calculated and reported a Cronbach’s alpha ( n = 67), and two studies calculated and reported a person separation index. The quality of internal consistency calculations was rated as “very good” in 64 studies [ 36 39 , 41 45 , 47 – 63 , 66 , 67 , 69 , 71 81 , 83 , 84 , 86 , 88 92 , 94 , 95 , 97 , 99 102 , 104 106 , 108 , 110 ] and as “inadequate” in five studies [ 46 , 60 , 98 , 109 , 111 ]. Inadequate ratings were given when a Cronbach’s alpha was not reported for each unidimensional subscale in a multidimensional instrument [ 31 ].…”
Section: Resultsmentioning
confidence: 99%